Complete chloroplast genome sequence and annotation of Actinodaphne lecomtei C.K.Allen, 1938 (Lauraceae). Issue 3 (4th March 2022) - Chen, Zimeng; He, Li; Weicai, Song; Shi, Wenbo; Gong, Qin; Shi, Chao
Abstract: Actinodaphne lecomtei C.K.Allen, 1938 is an evergreen tree of the Lauraceae family and grows at the mountainous areas of southwestern China. In this study, we presented the first complete chloroplast genome sequence of A. lecomtei. We analyzed the chloroplast genome structure of A. lecomtei and performed a phylogenetic analysis. The complete chloroplast genome of A. lecomtei was 152, 863 bp in length which contains a large single-copy (LSC) region of 93, 763 bp, a small single-copy (SSC) region of 18, 814 bp, and two inverted repeat (IR) regions of 20, 143 bp. The analysis identified 128 genes, comprised of 84 protein-coding genes, 36 tRNAs, and eight rRNAs. The GC content of A. lecomtei complete chloroplast genome was 39.1%. The phylogenetic analysis result demonstrated that A. lecomtei was closely related to A. obovate.